Glycemic Control and Clinico-Electrophysiological Severity of Diabetic Polyneuropathy (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Diabetic polyneuropathy (DPN) has a significant positive correlation with poor glycemiccontrol (HbA1c ≥7%). The clinical, biochemical and electrophysiological parameters of DPN in Bangladeshi citizens have not yet been explored elaboratelyObjective: The purpose of the study was to detect and categorize status of glycemic control of Bangladeshi people and to analyze its impact on clinical severity of DPN using Toronto Clinical Scoring System (TCSS) and electrophysiological severity by modified Michigan diabetic neuropathy score (MDNS).Methodology: This observational study was carried out on diabetic patients having probable DPN by purposive sampling, attending Neurology OPD of Dhaka Medical College Hospital, Dhaka, Bangladesh and Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine & Metabolic Disorder (BIRDEM) Hospital, Dhaka, Bangladesh from July 2014 to June 2016. Clinical parameters were recorded and DPN was graded as “no neuropathy”, “mild”, “moderate” and “severe” neuropathy by the Toronto Clinical Scoring System (TCSS). A standard nerve conduction study was performed on each patient and electrophysiological grading according to modified Michigan diabetic neuropathy score (MDNS) was done. Diabetic status of patients was classified into “controlled” (HbA1c